Bioactive polymethylmethacrylate bone cement modified with combinations of phosphate group-containing monomers and calcium acetate. (April 2015) - Liu, Jinkun; Shirosaki, Yuki; Miyazaki, Toshiki
Bone cement from polymethylmethacrylate powder and methylmethacrylate liquid has been successfully demonstrated as artificial material to anchor joint replacements in bone. However, it lacks the capability to bond directly to bone, so long-term implantation leads to an increased risk of loosening. Bioactive materials show better performance in fixation to bone, and the chemical bonding depends on bone-like apatite formation. This is triggered by surface reactions with body fluid. For these reactions, superficial functional groups like silanol (Si–OH) are ideal sites to induce apatite nucleation and the release of Ca 2+ ions accelerates the apatite growth. Therefore, incorporation of materials containing these key components may provide the cement with apatite-forming ability. In this study, phosphoric acid 2-hydroxyethyl methacrylate ester or bis[2-(methacryloyloxy)ethyl] phosphate supplying a phosphate group (PO4 H2 ) was added into methylmethacrylate liquid, while calcium acetate as a source of Ca 2+ ions was mixed into polymethylmethacrylate powder. The influences of the combinations on the setting time and compressive strength were also investigated. Apatite was formed on the cements modified with 30 mass% of phosphoric acid 2-hydroxyethyl methacrylate ester or bis[2-(methacryloyloxy)ethyl] phosphate. The induction period was shortened with increased amounts of Ca(CH3 COO)2 . The setting time could be controlled by the Ca(CH3 COO)2 /monomer mass ratio. Faster setting was achieved at a ratio close to the mixing ratio of the powder/liquid (2:1), and both increases and decreases in the amount of Ca(CH3 COO)2 prolonged the setting time based on this ratio. The highest compressive strength was 88.8 ± 2.6 MPa, higher than the lowest limit of ISO 5833 but was lower than that of the simulated body fluid-soaked reference. The increase of additives caused the decline in compressive strength. In view of balancing apatite formation and clinical standard, bis[2-(methacryloyloxy)ethyl] phosphate is more suitable as an additive, and the optimal modification is a combination of 30 mass% of bis[2-(methacryloyloxy)ethyl] phosphate and 20 mass% of Ca(CH3 COO)2 .